Assessing Lecturer’s Understanding of Plagiarism: A Case in Indonesia - Wihardini, Diah (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
Plagiarism, a concept of intellectual property in academic writing, has gained importance during the past few years in Indonesian higher education system. The vague definition and understanding of plagiarism have seemed to induce inconsistent efforts in preventing plagiarism practices in the local tertiary institutions (Akbar and Picard, 2019). This study aims to introduce and describe the step-by-step process in developing an assessment instrument that can measure a university lecturer’s understanding of plagiarism concept. A Rasch’s partial credit model was used in the data analysis to explain the different levels of the hypothesized understanding of plagiarism construct. Not only that the findings can help ones to learn the necessary steps to develop the instrument that upholds standards of reliability and validity, they can also provide good insights for the university authority to set an appropriate training for the lecturers on plagiarism prevention and mitigation as the different levels of these lecturers’ understanding of plagiarism are unpacked and addressed.